Circulating microRNAs as diagnostic and therapeutic biomarkers in gastric and esophageal cancers - Jamali, Leila; Tofigh, Roghayeh; Tutunchi, Sara; Panahi, Ghodratollah; Borhani, Fatemeh; Akhavan, Saeedeh; Nourmohammadi, Parisa; Ghaderian, Sayyed M.H.; Rasouli, Milad; Mirzaei, Hamed (Journal of cellular physiology, 2018)
Gastric and esophageal cancers are as main cancers of the gastrointestinal (GI) tract, which are associated with poor diagnosis and survival. Several efforts were made in the past few decades to finding effective therapeutic approaches, but these approaches had several problems. Finding new biomarkers is a critical step in finding new approaches for the treatment of these cancers. Finding new biomarkers that cover various aspects of the diseases could provide a choice of suitable therapies and better monitoring of patients with these cancers. Among several biomarkers tissue specific and circulating microRNAs (miRNAs) have emerged as powerful candidates in the diagnosis of gastric and esophageal cancers. MiRNAs are small noncoding single‐stranded RNA molecules that are found in the blood and regulate gene expression. These have numerous characteristics that make them suitable for being used as ideal biomarkers in cancer diagnosis. Research has indicated that the level and profile of miRNA in serum and plasma are very high. They are potentially noninvasive and sensitive enough to detect tumors in their primary stages of infection. Multiple lines of evidence indicate that the presence, absence, or deregulation of several circulating miRNAs (i.e., let‐7a, miR‐21, miR‐93, miR‐192a, miR‐18a, and miR‐10b for gastric cancer, and miR‐21, miR‐375, miR‐25‐3p, miR‐151a‐3p, and miR‐100‐3p for esophageal cancer) are associated with initiation and progression of gastric and esophageal cancers. The aim of this review is to highlight the recent advances in the roles of miRNAs in diagnosis and treatment of gastric and esophageal cancers. The aims of this review is to highlight the recent advances in the roles of microRNAs in diagnosis and treatment of gastric and esophageal cancers.